Semiconductor Physics 2017
DOI: 10.1007/978-3-319-06540-3_8-2
|View full text |Cite
|
Sign up to set email alerts
|

Bands and Bandgaps in Solids

Abstract: Valence and conduction bands and the bandgap in between these bands determine the electronic properties of solids. For semiconductors, the band structure of the conduction band and the valence bands near the edge to the fundamental bandgap is of particular interest. Both the band structure and bandgap are influenced by K. W.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 101 publications
1
3
0
Order By: Relevance
“…LO and ω TO were achieved by determining the edge of Reststrahlen band, and ε ∞ was determined by analyzing the change trend of real part ε 1 at high frequency. According to SE experiments, it is found that the ε ∞ of GaN is almost temperature-independent with a value of 5.33, which is consistent with the 5 35. given by ref 26.…”
supporting
confidence: 88%
“…LO and ω TO were achieved by determining the edge of Reststrahlen band, and ε ∞ was determined by analyzing the change trend of real part ε 1 at high frequency. According to SE experiments, it is found that the ε ∞ of GaN is almost temperature-independent with a value of 5.33, which is consistent with the 5 35. given by ref 26.…”
supporting
confidence: 88%
“…E 0 is the band gap at 0 K, while α and β are empirical fitting parameters. 44 The wide use of the approximation in eq 1 is due to the complexity of the dependence of the band gap on temperature and the lack of a microscopic theory. Equation 1 fails to fit the specific PL(T) curve of CsPbBr 3 NCs (Figure 3b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is impossible to create a universal equation to describe the temperature dependence of any band gap. 44 We have previously described the effects of temperature on PL linewidth and band gap in terms of phonon coupling. 34 The two main factors in the shift in band gap are thermal expansion of the lattice and electron−phonon interaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation